Phosphorus Fertilization and Chemical Root Pruning: Effects on Root Traits During the Nursery Stage in Two Mediterranean Species from Central Chile - Fiorella Calderón-Ureña; Carolina Álvarez-Maldini; Manuel Acevedo; Manuel E. Sánchez-Olate; R. Kasten Dumroese; Antay Sierra-Olea; Juan F. Ovalle; Edwin Esquivel-Segura (Plants)
The role of a plant root system in resource acquisition is relevant to confront drought events caused by climate change. Accordingly, nursery practices like phosphorous (P) fertilization and root pruning have been shown to modify root architecture; however, their combined benefits require further investigation in Mediterranean species. We evaluated the effect of applied P concentrations (0, 15, 60, and 120 mg L−1 P) with or without chemical (copper) root pruning (WCu, WoCu, respectively) in Aristotelia chilensis and Quillaja saponaria on morpho-physiological and root architecture traits. Higher P concentration increased nutrient content in both species concurrent with higher growth. In A. chilensis, higher P concentrations only increased the length and volume of medium roots. In Q. saponaria, P additions increased root length and diameter and the length and volume of fine and medium roots. The root-to-shoot ratio declined with WCu in A. chilensis (23.1%) and Q. saponaria (15.7%). Unlike our hypothesis, fine root architecture remained unaffected with root pruning in A. chilensis, while fine root length and volume decreased with increasing P concentrations in Q. saponaria. Thus, P fertilization enhances root development more consistently than root pruning, highlighting the need for further testing under water deficit conditions to optimize nursery practices.